Factors that influence number of bids on finished cattle - Ted C. Schroeder; J. Mintert; R. Jones (Kansas Agricultural Experiment Station Research Reports, 1993)
Previous research indicates that the number of bids received on pens of fed cattle has a positive influence on price. This study was undertaken to determine what factors influence the number of bids received on pens of cattle. The number of bids for fed cattle was investigated in 13 southwestern Kansas feedyards during May through November, 1990. Results indicated that cattle of desired weight, with higher estimated carcass yield and quality grade, in larger pen sizes, and sold in the middle of the week received the most bids. In addition, feedyard asking price relative to packer price offers also influenced the number of bids received.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Marketing; Feed cattle; Bid Determinants; Number of bids